2012
DOI: 10.1016/j.eurpsy.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of vagus nerve stimulation in the treatment of depression: Variable results based on study designs

Abstract: Currently, insufficient data are available to describe VNS as effective in the treatment of depression. In addition, it cannot be ruled out that the positive results observed in the uncontrolled studies might have been mainly due to a placebo effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
45
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 46 publications
2
45
0
4
Order By: Relevance
“…Dysfunctions of the ANS were found in acute and chronic stressful conditions [10][11][12], insomnia [13,14], epilepsy [15,16], parkinsonisms [17,18], psychosomatic disorders [19] and schizophrenia, anxiety and mood disorders [6,[20][21][22][23][24], which are typically considered CNS-related conditions. Moreover, vagal nerve stimulation has been shown as an effective treatment for major depression [25,26], while relaxation techniques based on cardio-feedback are used for managing negative emotions and psychological symptoms [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunctions of the ANS were found in acute and chronic stressful conditions [10][11][12], insomnia [13,14], epilepsy [15,16], parkinsonisms [17,18], psychosomatic disorders [19] and schizophrenia, anxiety and mood disorders [6,[20][21][22][23][24], which are typically considered CNS-related conditions. Moreover, vagal nerve stimulation has been shown as an effective treatment for major depression [25,26], while relaxation techniques based on cardio-feedback are used for managing negative emotions and psychological symptoms [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Vagal nerve stimulation (VNS) has been introduced or tested as a therapy for a range of disorders including epilepsy [1], cardiac arrhythmia [2], heart failure [3], depression [4], inflammatory bowel disease [5], rheumatoid arthritis [6] and obesity [7]. In the case of obesity, the vagal stimulation was designed to block the passage of afferent action potentials.…”
mentioning
confidence: 99%
“…Among these, deep-brain stimulation (DBS) has been the most documented especially for its use in treating obsessivecompulsive disorder and depression [6][7][8][9][10]. Vagal nerve stimulation (VNS), transcranial magnetic stimulation (TMS), and transcranial direct current stimulation (tDCS) have also gained popularity, notably for the treatment of refractory depression [11][12][13][14][15][16][17]. More recently, various studies have shown that these stimulation techniques could also be used for the treatment of fear-related disorders, such as PTSD [18•].…”
Section: Introductionmentioning
confidence: 99%